2005
DOI: 10.1093/brain/awh600
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative diffusion tensor imaging in cerebral palsy due to periventricular white matter injury

Abstract: Periventricular white matter injury (PWI) is a major form of brain injury observed in congenital hemiparesis. The aim of this study is to determine the usefulness of diffusion tensor imaging (DTI) and fibre tracking in delineating the primary and secondary degenerative changes in cerebral white matter and deep grey matter in patients with spastic cerebral palsy due to PWI and to look for any possible reorganization of the axonal architecture. Five hemiparetic cerebral palsy patients (median age 14 years) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
205
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(230 citation statements)
references
References 48 publications
18
205
1
5
Order By: Relevance
“…The basic idea of counting tracks has been around in diffusion MRI for several years (e.g., (Behrens et al, 2003;Roberts et al, 2005;Thomas et al, 2005)). These earlier studies used track-density quantification to estimate the probability of connection between regions, as a tool to parcellate brain structures from probabilistic tractography results, or as a summary parameter to characterise fibre bundles for intra-and inter-subject quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The basic idea of counting tracks has been around in diffusion MRI for several years (e.g., (Behrens et al, 2003;Roberts et al, 2005;Thomas et al, 2005)). These earlier studies used track-density quantification to estimate the probability of connection between regions, as a tool to parcellate brain structures from probabilistic tractography results, or as a summary parameter to characterise fibre bundles for intra-and inter-subject quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some authors showed by diffusion tensor MRI that apart from corticospinal tract damage, children with a periventricular lesion also had involvement of thalamocortical pathways. 32,33 Interestingly, recent imaging studies suggest that motor and sensory reorganization may be mediated by different forms of neuroplasticity. 30,34 Interhemispheric reorganization differences may account for the different levels of sensory and motor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…One of the definite advantages of DTI is the possibility of quantitative measurement of tract diameters and tract-specific DTI parameters 27,29,36,57,58 that will be attempted as a complementary study to the present one. However, one potential problem foreseen in these cases and previously discussed is partial volume effects due to the small brain size.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Results have provided further understanding of pathogenesis and treatment in a range of neurologic disorders by providing visualization of specific white matter fiber tracts (see review by Horsfield and Jones 22 ). [23][24][25][26][27] Although injury to the corticospinal tracts is thought to be the major determinant of motor impairment in children with PVL, recent studies have shown that sensory pathways, including the posterior thalamic radiation, may be affected instead or, concurrently, 28 indicative of the complexity of white matter involvement in PVL. 29,30 Criteria for DTI-based identification of various white matter tracts at 26 locations were established and applied to 24 children with CP associated with PVL as well as in a group of 35 unaffected controls to further elucidate the diversity of white matter tract injury involvement in PVL.…”
mentioning
confidence: 99%